2005
DOI: 10.1159/000089522
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Possible Disease Mechanisms of an Under-Recognized Fungus, <i>Aureobasidium pullulans</i>

Abstract: Background: Investigations into the occurrence and health effects of yeast-like fungi in the outdoor air in the US have been limited. We sought to identify a respirable-sized fungus common in the Pasadena air, locate a major source for the emissions and investigate its relevance to allergic disease. Methods: Yeast-like fungi sampled from the environment were isolated, microscopically examined and sequenced. Pasadena allergy patients were skin tested with commercially available fungal extracts. Patient serum wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…It has been found in most habitats and is prominent in the phyllosphere. It is also airborne (Shelton et al 2002 and has been implicated as a major cause of allergic disease in humans; recent studies on conidia emitted from flowers suggest high-molecular weight allergens in A. pullulans are responsible (Taylor et al 2005). Aureobasidium pullulans has been used for the production of extracellular compounds, especially polysaccharides such as pullulan (Catley 1979) and enzymes (Buzzini and Martini 2002).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found in most habitats and is prominent in the phyllosphere. It is also airborne (Shelton et al 2002 and has been implicated as a major cause of allergic disease in humans; recent studies on conidia emitted from flowers suggest high-molecular weight allergens in A. pullulans are responsible (Taylor et al 2005). Aureobasidium pullulans has been used for the production of extracellular compounds, especially polysaccharides such as pullulan (Catley 1979) and enzymes (Buzzini and Martini 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Aureobasidium pullulans is involved as the principal colonizer initiating biodeterioration (e.g. plasticized polyvinyl chloride, Webb et al 2000) has been used as an indicator of environmental pollution (Deshpande et al 1992) and is implicated in human disease (Taylor et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Germany showed that this genus was associated with hypersensitivity pneumonitis, (59) and Taylor et al (60) reported that 16 out of 94 patients at the Asthma and Allergy Center in Pasadena, California, had a positive skin test reaction to A. pullulans extract. Stark et al (11) reported that high levels of Aureobasidium (>24,000 CFU/g or >90th percentile concentration for that study) were associated with allergic rhinitis in 5-year-old children.…”
Section: Culturable Fungal Levels Related To Health Effectsmentioning
confidence: 99%
“…have been described as yeast-like fungi, which produce yeast-like hyaline conidia and a filamentous growth form (Taylor et al 2006). This genus was established in 1891 by French scientists Viala and Boyer (Cooke 1959).…”
Section: Introductionmentioning
confidence: 99%